Mineralogical, Elemental, and Spatial Variability of Volcaniclastics in Fluvio‐Coastal‐Aeolian Sedimentary Systems and Their Insights for Mineral Sorting on Mars - Ignatius Argadestya; Abduljamiu O. Amao; Candice C. Bedford; Pantelis Soupios; Khalid Al‐Ramadan (Earth and Space Science, 2022)
Abstract This study investigates the mineralogical, elemental, and spatial variability from source (proximal) to sink (distal) of Merapi basalt‐andesitic stratovolcano (Java, Indonesia) to better constrain volcaniclastic mineral sorting in fluvial, aeolian, and coastal environments. Merapi volcaniclastics are products of an active volcano with an ongoing quadrennial eruption, which can provide insights to constrain Mars' older and more recent volcaniclastics by focusing on anorthite, albite, and pyroxenes found on Mars' surface. We collected stream sediment samples across the Opak River that connects Merapi with the Indian Ocean. In addition to grain size analysis, all collected samples were subjected to X‐ray diffractometer and X‐ray fluorescence to quantify their mineralogical and elemental composition, respectively, like the CHEMIN instrument used by the Curiosity rover on Mars to investigate the geochemistry and mineralogy of geological units in Gale crater. Implementation of multivariate statistical analysis based on principal component analysis and Hierarchical Clustering of Principal Component are able to discriminate between fluvial, fluvio‐coastal‐aeolian, and marine influenced deposits. The quantitative assessment shows that the dominant mineralogy is influenced by pyroclastic materials dominated by plagioclase feldspars (albite and anorthite), followed by pyroxenes (augite and enstatite). Alteration modeling of Merapi samples favors a fluvial depositional environment rather than mass‐wasting from the crater rim for Gale crater rocks (i.e., Pahrump Hills, Hartmann's Valley, Karasburg, Sutton Island member) on Mars.